2006
DOI: 10.1079/phn2005762
|View full text |Cite
|
Sign up to set email alerts
|

Why are rural Indian women so thin? Findings from a village in Maharashtra

Abstract: Objective: To identify social, behavioural and cultural factors that explain the thinness of young women relative to their men in rural Maharashtra, India. Design: Twelve focus group discussions were conducted to explore the villagers' understanding of why women in their area might be thinner than men. Setting: Pabal village and surrounding hamlets, in the Pune district of Maharashtra, India. Subjects: Samples of young mothers and fathers, grandmothers and grandfathers were selected from families in the villag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 23 publications
0
46
0
Order By: Relevance
“…This is the picture of the developing world where women neglect their own health. 18 Social roles prevent women from practicing exercise. They have no time from their work.…”
Section: Discussionmentioning
confidence: 99%
“…This is the picture of the developing world where women neglect their own health. 18 Social roles prevent women from practicing exercise. They have no time from their work.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a cross-sectional survey from 2001 to 2003 of 3,000 women aged 18–45 years in Goa, India found indicators of gender disadvantage such as an early age at marriage and childbearing, low levels of decision-making autonomy, family support, and sexual violence by husbands increased the prevalence of mixed-anxiety depressive disorder ( 102 ). Another qualitative sub-study of the rural Pune Maternal Nutrition Study conducted 12 separate focus group discussions with young mothers and fathers, grandmothers and grandfathers in 1998 ( 103 ). It found that young mothers had poor nutritional status and experienced anxiety and depression because their minimal influence over the allocation of resources restricted access to health services, and social isolation prevented them from caring for their children’s health and education.…”
Section: Consequences Of Women’s Under-age Marriagementioning
confidence: 99%
“…Between 1994 and1996, a study of women living in villages near Pune city in western India was carried out to examine the relationship of maternal nutrition to fetal growth (4-6). The study showed that thinner women had thinner babies, and also found women to be significantly thinner than their husbands (7); 65% of women had body mass indices (BMIs) below 18.5 kg/m 2 , an indicator of chronic energy deficiency, compared with 39% of their husbands.…”
Section: Introductionmentioning
confidence: 99%
“…Though it seems likely that this role affects women’s nutritional status, there is little direct evidence to link the two. Villagers in rural Maharashtra believed their women were thin because of the combined demands of early motherhood and work (7). This paper describes an attempt to identify the social and economic correlates of thinness among young women in this population (the first survey), and to explore how women’s daily activities might contribute to this phenomenon (the second survey).…”
Section: Introductionmentioning
confidence: 99%